Sustainable Development in English Language Teaching: Prevailing Trends, Challenges, and Outcomes - Azizah, Nurul Latifatul; Ali Mustofa; Pratiwi Retnaningdyah (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
The current trends, challenges, and outcomes of integrating the Sustainable Development Goals into English Language Teaching (ELT) are examined in this review. This study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique and systematically reviewed 25 research articles identified through a targeted search with keywords such as "SDGs," and "ELT." The data set includes 25 articles sourced from Taylor Francis, ScienceDirect, and Google Scholar, covering publications between 2020 to 2024. Findings reveal that integrating SDGs in ELT content fosters critical thinking, empathy, and engagement among students, enhancing both their language skills and global citizenship values. Despite the benefits, there are challenges, including limited awareness of SDGs, inadequate resources, and alignment issues with language curriculum goals. The review highlights positive outcomes in student engagement and language acquisition when SDGs content is incorporated, as well as increased motivation among teachers to pursue sustainability-oriented pedagogies. Future recommendations stress the need for continuous teacher training, the development of interdisciplinary approaches, and institutional support to facilitate meaningful SDGs integration in ELT.